JELLY CANDY PRODUCTION WITH VARIATIONS OF BROCCOLI (Brassica oleracea var. italica) AND RED GINGER (Zingiber officinale var. rubrum Theilade) - Jamilatun, Makhabbah; Purnamasari, Tiara; Tolkhah, Ronal (Poltekkes Kemenkes Surakarta, 2024)
Candy is a snack that is loved by almost everyone of all ages. Jelly candy is a candy made from vegetable or fruit essence, forming a gel, with a soft texture, clear color, and a certain level of elasticity. Broccoli (Brassica oleracea var. italica) contains vitamins, folate, phosphorus, magnesium, iron, potassium, and calcium. Red ginger (Zingiber officinale var. rubrum Theilade) contains gingerol compounds, flavonoids, phenols, terpenoids, and essential oils. The purpose of this study was to determine the organoleptic characteristics, water content, and reducing sugar jelly candy with variations of broccoli and red ginger. This study uses a quantitative experimental method. The research procedures included preparing broccoli, preparing red ginger, making jelly candy with 3 formulas, and evaluating jelly candy. The results showed that the organoleptic of the three jelly candy formulas had a distinctive aroma of broccoli and red ginger, brownish green color, spicy-sweet taste, and chewy texture. The water content of the jelly candy in the three formulas was 17.22% (F1), 18.33% (F2), and 18.17% (F3) respectively. Reducing sugar for jelly candy in the three successive formulas was 18.6% (F1), 16.3% (F2), and 19.3% (F3). The water content and reduced sugar of jelly candy with variations of broccoli and red ginger have met the quality requirements for soft confectionery, SNI 3547-2-2008. The results in this study, the water content and reducing sugar were below the maximum number of predetermined soft confectionery quality requirements.